Aspek Sosial dalam Novel Surat Wasiat Karya Samsoedi - Muliawati, Ema Siti; Nurjanah, Nunuy; Isnendes, Retty (JENTERA: Jurnal Kajian Sastra, 2023)
This research was conducted due to the lack of public awareness in appreciating literary works that are full of social values. The purpose of this study is to describe the social elements contained in the novel Surat Wasiat by Samsoedi. In this research, the descriptive analysis method is used, which involves collecting data from the novel Surat Wasiat, analyzing the collected data, and presenting a description of the data. The main source of data in this research comes from the novel Surat Wasiat.  The data obtained is a record of the results of analyzing the literature that has been studied. The results of this study identified three social dimensions, including religious, economic, and educational aspects. In the religious social dimension, three related elements were identified, including 1) belief in Allah Swt, 2) obeying His commands, and 3) sincere attitude and gratitude to Him. In the social dimension of education, there are six elements, including 1) ethics, 2) respect, 3) patriotism, 4) peace, 5) avoiding envy and jealousy, and 6) complying with prevailing social norms. AbstrakPenelitian ini dilakukan karena kurangnya kesadaran masyarakat dalam menghargai karya sastra yang sarat dengan nilai-nilai sosial. Tujuan dari penelitian ini adalah untuk menguraikan elemen-elemen sosial yang terdapat dalam novel Surat Wasiat karya Samsoedi. Dalam penelitian ini, digunakan metode analisis deskriptif yang melibatkan pengumpulan data dari novel Surat Wasiat, proses analisis terhadap data yang terhimpun, serta penyajian deskripsi dari data tersebut. Sumber utama data dalam penelitian ini berasal dari novel Surat Wasiat.  Data yang didapatkan adalah catatan dari hasil analisis literatur yang telah diteliti. Hasil dari penelitian ini mengidentifikasi tiga dimensi sosial, meliputi aspek keagamaan, ekonomi, dan pendidikan. Dalam dimensi sosial keagamaan, teridentifikasi tiga elemen terkait, termasuk 1) keyakinan pada Allah Swt, 2) mematuhi perintah-Nya, serta 3) sikap ikhlas dan rasa syukur kepada-Nya. Dalam dimensi sosial pendidikan, terdapat enam unsur, di antaranya 1) etika, 2) sikap menghargai, 3) patriotisme, 4) kedamaian, 5) menghindari rasa iri dan dengki, serta 6) patuh pada norma-norma sosial yang berlaku.